Scheduled state feedback control of a wind turbine. Issue 2 (September 2020) - Engels, W. P.; van der Hoek, D.; Yu, W.; Reyes Baez, R.
Abstract: Many wind turbines are still controlled using gain scheduled, PI(D) controllers. Another option is to use a state feedback controller, such as LQG control. However, for wind turbines that is not straight forward solution, because the system is non-linear and the impact of pitching on the states varies in time. This paper presents a variation on state feedback control. An Extended Kalman Filter is combined with gain scheduling of the state feedback gains depending on aero-dynamic sensitivities, which enables an approximation of non-linear control. This controller structure is intended to be used in more comprehensive controller optimisation studies. The scheduled state feedback controller shows good behaviour and can outperform the original PID controller.